2002
DOI: 10.1172/jci15745
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid-stimulating autoantibodies in Graves disease preferentially recognize the free A subunit, not the thyrotropin holoreceptor

Abstract: Graves disease is directly caused by thyroid-stimulating autoantibodies (TSAb’s) that activate the thyrotropin receptor (TSHR). We observed upon flow cytometry using intact cells that a mouse mAb (3BD10) recognized the TSHR ectodomain with a glycosidylphosphatidylinositol (ECD-GPI) anchor approximately tenfold better than the same ectodomain on the wild-type TSHR, despite the far higher level of expression of the latter. The 3BD10 epitope contains the N-terminal cysteine cluster critical for TSAb action. Conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(25 citation statements)
references
References 57 publications
(32 reference statements)
1
23
1
Order By: Relevance
“…This approach developed from the observations suggesting that the TSHR A-subunit, rather than the full-length receptor, appears to be the primary autoantigen initiating and/or enhancing induction of TSAb [6]. We now demonstrate that a higher disease incidence is achieved by injecting DCs infected with adenovirus expressing the TSHR A-subunit (AdTSHR289) than adenovirus expressing the full-length TSHR [3].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This approach developed from the observations suggesting that the TSHR A-subunit, rather than the full-length receptor, appears to be the primary autoantigen initiating and/or enhancing induction of TSAb [6]. We now demonstrate that a higher disease incidence is achieved by injecting DCs infected with adenovirus expressing the TSHR A-subunit (AdTSHR289) than adenovirus expressing the full-length TSHR [3].…”
Section: Discussionmentioning
confidence: 91%
“…Recently, it was observed that TSAb in human sera bind preferentially to the TSHR ectodomain tethered to the cell membrane by a glycosylphosphatidylinositol-anchor versus the same ectodomain in the wild-type TSHR [6]. These findings raised the possibility that the shed A-subunit, rather than the full-length receptor, was the autoantigen responsible for the induction of TSAb.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, binding of auto-antibodies against the ectodomain of the TSH receptor, as it occurs in the Grave's disease, may lead to enhancement of the receptor constitutive activity, even in the absence of TSH (Chazenbalk et al 2002). Similarly, the occasional occurrence of certain mutational changes in b 2 -adrenergic receptors may render the receptor tertiary structure more unstable and therefore more readily adjustable to constitutively active states (Wilbanks et al 2002).…”
Section: The Emerging Interpretantmentioning
confidence: 99%
“…Results of many studies pointed to conformational nature of the epitopes (8 -10). The study of Rapoport's group, involving mutagenesis of four cysteines in positions 24, 29, 31, and 41, has presented evidence that disulfide bonds between C 41 and either C 29 or C 31, but not C 24, are important for the TSHR autoantibodies' stimulatory function (8,9). The cysteine-rich amino terminus of the TSHR was also the immunodominant linear antibody epitope in a murine model of Graves' hyperthyroidism (11).…”
Section: Introductionmentioning
confidence: 99%